EDUKASI TRI HITA KARANA DALAM PERTUNJUKAN DRAMA GONG PENOPANG KEBERLANJUTAN BUDAYA BALI - I Wayan Sugita (Pangkaja: Jurnal Agama Hindu, 2021)
This article aims to discuss the education of Tri Hita Karana (THK) in the drama gong performance in the era of society 5.0 and its meaning for the sustainability of Balinese culture. This article is the result of a qualitative study whose data were collected through observation, document studies, and in-depth interviews with performers and representatives of the audience of drama gong, as well as observers of Balinese arts and culture. Qualitative descriptive analysis was carried out by applying semiotic theory, symbolic interactionism theory, and social action theory (Bourdieu). The results of the study show that traditional Balinese performing arts function as a medium of entertainment and education of Balinese culture, especially about the philosophy of THK to its fans. Through three drama gong stories, namely "Jayaprana", "Ni Diah Tantri" and "Cupak Madeg Ratu" have succeeded in entertaining as well as delivering education on THK, so that Balinese people are able to realize a harmonious life: between humans and God (parahyangan ), humans with each other (pawongan), and humans with nature (palemahan). THK education through drama gong performances has a meaning in strengthening traditions and sustaining the cultural sustainability of the Balinese Hindu community.